Estimation of Photosynthetic Pigments in the Leaves of Crambe Spp. During Vegetation - Vergun, Olena; Rakhmetov, Dzhamal; Shymanska, Oksana; Fishchenko, Valentyna (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
This study investigated the content of chlorophyll a (Chl a), b (Chl b), carotenoids (car) and their ratio in four species of Crambe L. during vegetation: C. cordifolia Steven, C. koktebelica (Junge) N.Busch, C. maritima L., C. steveniana Rupr. collected in the M.M. Gryshko National Botanical Garden of the NAS of Ukraine (Kyjiv). The middle height increment of investigated plants between stages of growth is measured. The concentration of chlorophylls a, b and car measured spectrophotometrically on UNICO 2800 at the wavelength 662, 644 and 440, respectively. Extraction procedure conducted in acetone. Obtained results are given in mg/g of fresh mass. The height increment in a period of spring vegetation-budding was 26.3–80.2 cm, budding-flowering 12.3–136.0 cm, flowering-fruitage 1.3–16.6 cm depending on species. C. cordifolia had the most value of this parameter at the budding–flowering period and C. maritima had the least value at the flowering–fruitage period. Content of Chl a at the spring vegetation period was 0.321–0.490 mg/g, at the budding period 0.237–0.680 mg/g, at the flowering period 0.349–0.680 mg/g and at the fruitage 0.478–0.962 mg/g depending on species. Content of Chl b was 0.133–0.203 mg/g at the spring vegetation stage, 0.158–0.275 mg/g at the budding stage, 0.158–0.275 mg/g at the flowering stage and 0.227–0.439 mg/g at the fruitage depending on species. The concentration of car was 0.038–0.078 mg/g at the spring vegetation period, 0.043–0.104 mg/g at the budding period, 0.070–0.201 mg/g at the flowering period and 0.117–0.435 mg/g at the fruitage depending on species. Correlation between the content of Chl a and increment of plants was strong at the spring vegetation (r = 0.78), moderate at the budding period (r = 0.52) and strong at the flowering (r = 0.76). At the flowering stage found a very strong correlation (r = 0.90) between Chl b content and increment of plants. Thus, obtained data showed that between the accumulation of photosynthetic pigments of investigated plants and increment of plants exists a positive correlation, which depends on the period of growth. Further, it’s can be used for the study of total productivity and some grow parameters of these plants.